Soda Anthraquinone (Soda AQ) and Bio-chemical pulping process on napier grass for papermaking industry - Mohd Hatta, Mohd Zainuri (2018)
Nowadays, our nature sources become decrease where effect to paper industry. Thus, use of non wood (Napier grass) as a base material by an additive should became an alternative fibre for papermaking industry. The aim of this study to analyse the chemical composition of Napier grass; to determine the effects of different optimization pulping process on the pulpability and mechanical properties; to determine the surface characterization of paper by different pulping process. Napier grass sample would be undergoing of different pulping process (Soda-AQ pulping, Bio-chemical and combination pulping). The chemical properties involved in this study were determined according to relevant TAPPI test, Kurscher–Hoffner and Chlorination methods. Meanwhile, fibre dimension and pulp properties were measured after the pulping process. The mechanical strength of handsheet produced (tensile, burst, tear and fold) was investigated according to the TAPPI test method. Scanning Electron Microscope (SEM) was used to determine the morphological characteristic of the Napier grass paper. Results show high cellulose (60.2%); 1% NaOH solubility (52.0%) and lower of lignin (10.7%); ash (14.1%) and hemicellulose (23.8%) contents of Napier grass. The best optimum condition from pulpability and mechanical analysis were 16% concentration of alkali charge, 160 0C of temperature. Optimization pulping combination both dosage made a remarkable of high pulp yield produce (38.88%), low rejected pulp (5.2%), by a lower kappa index number (13.42%) and short fibre length (8.2%) from pulpability and mechanical properties for tearing strength, 5.58 Nm2/g; high folding endurances, 987 Nm; high burst strength, 358.2 kPa*m2/g; and higher of tensile strength, 5.11 Nm/g compared to single additives. Fibre structure image from combination dosage by SEM had completely different with a treatment by anthraquinone and xylanase enzyme act as a factor which lead a highly strong fibre to produce a good paper from non-wood materials to be compete with a wood-base paper for industry. Napier grass by the additional of additives from anthraquinone and xylanase enzyme could makes a confirmation for this agriculture plant to be an alternative fibre for pulp and papermaking industry for future.